BUILDING COMPOSITES AS OBJECTS OF SYSTEM ANALYSIS (MODERN CONSTRUCTION AND ARCHITECTURE, 2023)
The article is devoted to the consideration of the material science problems from the standpoint of the general systems theory. The method of dialectical pairs "part-whole", "continuous-discrete" and "randomness-necessity" is used, corresponding to the general system coordinates, on the basis of which the third emergent component of a synthetic nature arises. System-theoretic methods make it possible to concretize model representations using elements of the crystallization theory of dynamic information theory. System representations are used to refine the concept of an interface in materials and heterogeneous systems. The dialectical unity of atomistic and geometric concepts in the theory of the formation of a new phase in binders is shown. The probabilistic and informational description is considered as a realization of the dialectical pair "randomness-necessity". The concept of information is closely related to choosing one or more options from many and remembering the choice made. The choice can be made as a result of the action of external forces (information reception) or due to the unstable behavior of the system (the emergence of new information). The process of structure formation can be considered as the dynamics of an information system. The dynamics of the information system should include interactions that provide any structure-forming particle with the possibility of transition between the areas of influence of stable states with subsequent attraction to one of them. The formation of structures in a binder from the position of dynamic information theory is considered as the reception of information. It is necessary to perform work, due to which the system will go into one of the stable states for the reception of information. The formation of new elements and structures ‒ pores, capillaries and cracks is considered as a transition of the system to its own potential minima ‒ the epigenetic landscape of the material as an emerging system. In this case, part of the energy will be lost in the process of dissipation, and the physical entropy will increase by a value exceeding the amount of information received. Such an effect can be considered as the "price" of the observed macroscopic process of self-organization. The involvement of systems theory also helps, on the basis of the principle of adequacy, to indicate the way for choosing a model object that is optimal for studying the processes of structural transformations of a material.
Keywords: composite building materials; dispersed systems; system approach; structure formation; dialectical pairs.